Effects Of Liquidity On Firm\'s Cost Of Equity In Malaysian Stock Market - Askarzadeh, Shadi (2010)
This research examines the contemporaneous relation between liquidity and cost of equity capital of individual firms listed in the Trading and Service sector of Bursa Malaysia from 2005-2009 using pool (OLS) regression. The result indicates a significant negative relationship between stock liquidity and firms\' cost of equity capital in the Malaysian corporate sector.